2006
DOI: 10.1111/j.1423-0410.2005.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen inactivation of Leishmania donovani infantum in plasma and platelet concentrates using riboflavin and ultraviolet light

Abstract: Background and Objectives  Leishmania is transmitted by the bite of the phlebotomine sandfly or by transfusion of infected blood products. Leishmaniasis currently poses a significant problem in several parts of the world, and is an emerging problem in others. The Mirasol PRT technology is based on the use of riboflavin and ultraviolet light to generate chemical reactions in the nucleic acids of pathogens, which prevents replication and leads to inactivation. The intent of this study was to examine the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
84
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 26 publications
3
84
0
2
Order By: Relevance
“…Multicenter trials by Cardo et al have shown the riboflavin method to be effective for killing Leishmania and other emerging plasma and platelet pathogens (5-7 log reduction). 6,7 Numerous studies have also confirmed this method to be effective for white blood cell inactivation. Clinical trials have proved the safety of Mirasol ® PRT system-treated blood components and lack of neoantigen formation.…”
Section: Introductionmentioning
confidence: 92%
“…Multicenter trials by Cardo et al have shown the riboflavin method to be effective for killing Leishmania and other emerging plasma and platelet pathogens (5-7 log reduction). 6,7 Numerous studies have also confirmed this method to be effective for white blood cell inactivation. Clinical trials have proved the safety of Mirasol ® PRT system-treated blood components and lack of neoantigen formation.…”
Section: Introductionmentioning
confidence: 92%
“…Using riboflavin as a photosensitizer, in combination with UV light, has been shown to reduce the infectivity of a broad range of pathogenic blood-borne contaminants, including bacteria 3,4,8,10,[19][20][21] .The use of riboflavin and UV light for pathogen reduction is non-toxic and non-mutagenic, and riboflavin and UV light-treated components have been shown to be safe for transfusion recipients as well as for those handling blood products 18 . Briefly, riboflavin molecules can associate with the nucleic acids (DNA and RNA) of bacteria, parasites, viruses and any nucleated cell (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using in vitro experiments several methods designed to inactivate Leishmania in blood products have been tested. These include the use of riboflavin (as a photosensitizer) and ultraviolet light [105], and the photochemical treatment by amotosalen plus ultraviolet light in platelet concentrates [106,107] as well as by thiopyrylium in RBC suspensions [108].…”
Section: Preventionmentioning
confidence: 99%
“…As a result of these photochemical processes, pathogens in blood products are rendered unable to replicate due to nucleic acid modification. This technology exploits the absence of nucleic acids in all the blood components (including plasma and platelet concentrates), which are beneficial to transfusion, and that instead is present in the parasite [105,109].…”
Section: Preventionmentioning
confidence: 99%